The Synergy Between Entrepreneurship Curriculum and Digital Literacy in Fostering Entrepreneurial Intentions Among College Students - Indah Rizki Maulia; Sumarno Manrejo; Ari Sulistyowati; Sugeng Suroso (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to explore whether the entrepreneurship curriculum and digital literacy can play a role in enhancing entrepreneurial intentions among students. The research was conducted using a quantitative method, with a sample of 65 college students who had already taken entrepreneurship courses. Data analysis was performed using SEM (Structural Equation Modeling) with SmartPLS 4.0. The results showed a positive and significant influence of the entrepreneurship curriculum and digital literacy on students' entrepreneurial intentions. The findings of this study are expected to serve as input for higher education institutions and digital platform managers to better play their roles in encouraging entrepreneurial intentions among students. Keywords: entrepreneurship curriculum, digital literacy, entrepreneurial intentions, college students